The discourses of risk of drug users in prison - R Clua-García; E Bañuls-Oncina; M Imbernón-Casas; R Jiménez-Vinaja (Sociedad Española de Sanidad Penitenciaria, 2019)
ABSTRACT Introduction and objectives: In the last twenty years, sociological changes and actions aimed at improving the health of inmates have contributed to decrease the prevalence of infectious diseases and overdoses among prison population. Currently, however, drug addictions treatment penitentiary programs are questioned for lacking of innovation and deficiencies in coverage. In order to investigate this issue we analyzed the discourses of imprisonned people regarding drug use and drug addiction programs. Materials and methods: We applied a qualitative phenomenological method. We carried out four discussion groups with 29 encarcerated drug users and made an analysis of the discourse about different possitionings towards drug use and drug addiction treatment programs. Results: From the combination of positions regarding drug use and drug addiction treatment programs emerged three kind of discourses respectively called: a) "reckless", characteristic of people implied in risk practices without taking preventive measures; b) "adventourous", tipical of those that take drugs both keeping the benefits of these practices and controls its negative consequences using prevention measures; c) "prudent", of abstainers or occasionally users that minimize risks and damages. Discussion: Encarcerated population accept drug use practices based on three risk discourses. The present study shows out that, in order to increase the effectiveness of drug policies in prison, drug treatement programs goals must be adapted to drug users particular economization of risk strategies.